The Effect Of Giving Various Kinds And Immersion Of ZPT On The Growth Of Tin Cuttings (Ficus carica L.). - Nur Azizatu Rohmah (Nabatia, 2021)
This study aims to determine the effect of giving various kinds and duration of ZPT immersion on the growth of tin plant cuttings (Ficus carica L.). This research was carried out in October - December 2020, at the Terdana Village, Pondok Kubang District, Central Bengkulu Regency. This study used a Factorial Completely Randomized Design (CRD) with two factors, the first factor was giving various PGR (Z) which consisted of Control, Rootone-F, Shallot Solution, Bamboo Shoots Solution, while the second factor was the duration of immersion of PGR which consisted of of 12 hours, 18 hours, 24 hours, each treatment was repeated 3 times. The results of the study were analyzed using Variety Analysis and if it had a significant effect, further tests were carried out using Duncan's Multiple Range Test (DMRT) level 5%. The results showed that there was an interaction between the administration of Rootone-F and the immersion time of ZPT 12 to 24 hours on the percentage of live cuttings of Tin (Ficus carica L.) plant. 12 WAP, root length, percentage of live cuttings and leaf area on cuttings growth of Tin (Ficus carica L.) PGR immersion time treatment was not able to increase shoot length 12 WAP, number of shoots 12 WAP, number of leaves 12 WAP, root length, percentage of cuttings Life and leaf area on the growth of cuttings of Tin (Ficus carica L.) It is recommended to increase the concentration of natural PGR so that it can be used as a substitute for Rootone-F.